Pemahaman Investasi, Motivasi Investasi Dalam Minat Masyarakat Berinvestasi Di Pasar Modal - Amelia Sekar Ayu Pramesti; Dara Kesumadewi; Zona Oktavia (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Many people think that investing in the capital market is only for the upper class and people who have a lot of funds. In fact, both upper-class and lower-class people can invest if they really want to do so. Therefore, this research was made with the aim of explaining the understanding and motivating people to invest in the capital market. This type of research is descriptive qualitative with a literature study approach. The data collection technique used is a literature study by searching for data related to the discussion in the title of this research through searching on google scholar. Analysis technique through the collection of previous research through google scholar. The results of this study are investing in the capital market there are still obstacles such as lack of education and lack of socialization, therefore the need to provide understanding so that people are motivated to invest in the capital market.